A reversible data hiding scheme using bit flipping strategy. (3rd March 2016) - Kumar, Rajeev; Chand, Satish
Abstract: In this paper, we propose a new reversible data hiding scheme which embeds the secret data into an image. It divides the cover image into blocks of two pixels each in raster scan order. We construct a location map for the cover image so that reversibility of the scheme can be ensured. The secret data bit-stream is divided into segments each of size 2 bits i.e., (00, 01, 10 and 11) and these segments are embedded onto blocks of the cover image. While embedding the secret data, the first LSB of the pixel(s) of the block are flipped according to the secret data bits which just change the pixel value maximum by 1. Our scheme can also hide the secret data in layers which consequently increases the hiding capacity without any degradation in image quality. This is the biggest advantage of our scheme. Experimentally, we obtain more than 50db PSNR and 1bpp hiding capacity for all the cover images. For the second embedding layer, the PSNR increases by 1db and continues to persists at 51db for subsequent embedding layers. The results demonstrate that our scheme performs much better than many existing data hiding scheme.